Refining method of high-lead crude copper
By using a composite decompressant composed of phosphate, pyrophosphate and silica reacts with impurities in the copper melt, efficient one-step directional removal of lead and other impurities is achieved, solving the difficulty of effective lead in copper smelting The problem of removal improves the stability and efficiency of refined copper production.
Patent Information
- Application Number
- CN202411383436.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-17
AI Technical Summary
During the existing copper smelting process, the difficulty of effective removal of lead lead causes thermal brittle cracking of the anode copper mold, large fluctuations in impurities, and low lead removal efficiency, resulting in increased copper loss and equipment loss, making it difficult to adapt to changes in the structure of copper smelting raw materials.
Use compound demixing agents, including phosphate, pyrophosphate and silica, as a new demixing agent, react with impurities Pb, As, Sb, Bi, etc. in the copper melt to generate slag phases to achieve one-step directional demixing Remove lead and other impurities.
It improves the efficient removal rate of lead, shortens the reaction time, reduces copper loss and production costs, and improves the production stability and process efficiency of refined copper.
Smart Images

Figure CN119320879A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nonferrous metal metallurgy, and in particular relates to a refining method for high-lead crude copper. Background Art
[0002] Copper is an important basic material and strategic material, and it plays an indispensable role in the fields of national economy and people's livelihood, national defense engineering, high-tech, etc. In recent years, with the rapid development of strategic emerging industries, high-end manufacturing and new energy vehicle industries, refined copper consumption has ushered in a new growth point. my country is the world's largest producer and consumer of refined copper. In 2023, my country's refined copper output will reach 12.99 million tons. However, my country's copper ore resources are limited, and copper smelting raw materials mainly rely on imports, and the external dependence of copper mines has exceeded 75%. In order to solve the serious shortage of copper ore resources, accelerating the recycling of secondary resources such as scrap copper has become an important measure to fill the gap in raw materials, and the proportion of scrap copper in the raw material structure has increased year by year. Due to the increasingly diversified structure of copper smelting raw materials, the content of associated impurities such as Pb, Sb, Bi, As, Zn, Sn, Fe, Si and O in the process of smelting, blowing or recycling scrap copper to prepare crude copper in copper ore increases year by year, and the difficulty of predicting, controlling and balancing raw material composition increases year by year, which has a significant impact on the preparation of pyrometallurgical anode copper and back-end electrolytic refining. Therefore, innovative smelting and impurity control technologies are an important development direction for copper smelting enterprises to adapt to changes in raw material structure and achieve industrial transformation and upgrading.
[0003] Lead is a common associated metal in copper metallurgy. The solubility of lead in copper liquid is very small. When in solid state, the solubility of lead in copper does not exceed 0.1%. The two are mechanically mixed. In addition, the crystallization temperature difference between copper and lead is large. Copper begins to crystallize at 960℃~1000℃, while lead needs to be cooled to 326℃ before crystallization. During solidification, sequential segregation will form, causing the anode copper mold to be hot brittle, cracked and deformed. In addition, the lead in the anode copper has the characteristics of enriching arsenic, antimony, bismuth, selenium, tellurium and other impurities to form a multi-component impurity precipitation phase, which makes the local impurity content of the anode plate fluctuate greatly, causing a series of problems such as anode passivation during the electrolysis process, excessive lead content in cathode copper and high anode mud yield. Therefore, removing the impurity lead in the copper melt is an important task in the pyrometallurgical refining process of crude copper. At present, in the pyrometallurgical refining of crude copper, the lead removal agent used is mainly white slag, the main component of which is silicon dioxide. During the lead removal process, SiO2 reacts with PbO in crude copper to generate a light-density xPbO·ySiO2 slag phase, which is separated from the crude copper. On the other hand, the pyrometallurgical refining process of crude copper often uses alkaline agents such as quicklime, calcium carbonate, sodium nitrate, and sodium hydroxide. The alkali reacts with As2O5, Sb2O5, etc. to form a light-density arsenate / antimonate slag phase, thereby skimming and removing the slag. Since the white slag (SiO2) is acidic, it is easy to react with the added quicklime and other alkaline agents to form a xCaO·ySiO2 slag phase, which seriously affects the lead removal effect. Therefore, the existing lead removal process is separated from the arsenic, antimony, and bismuth removal processes. Lead removal is mainly carried out in the anode furnace and an acidic slag system is used. Since the white slag exists in the furnace body in a solid form, and due to the structure and process characteristics of the anode furnace, the slag-making agent cannot fully contact with the impurities, and it is necessary to extend the reaction time to ensure the thoroughness of the impurity removal reaction. Generally, the slag-making temperature is controlled at around 1200-1250°C, which can easily lead to problems such as copper loss, extended operation time, and increased equipment loss. In addition, since alkaline slag is often used in the top-blown continuous blowing of copper matte or the side-blowing process of the horizontal converter, a large excess coefficient of white slag is required in the lead removal process of the anode furnace, resulting in large white slag loss and low lead removal efficiency. In view of the above-mentioned shortcomings of the existing technology, the present invention develops a refining method for high-lead crude copper, thereby achieving targeted lead removal and broad-spectrum removal of other impurities, thereby coping with changes in the structure of copper smelting raw materials, improving the stability of refined copper production, and reducing the unit operating cost of pyro-refining, which is of great significance to the copper industry to achieve high-quality development and enhance technical process development capabilities. Summary of the invention
[0004] In view of the above-mentioned shortcomings of the prior art, the present invention provides a method for refining high-lead blister copper.
[0005] To achieve the above object, the technical solution adopted by the present invention is:
[0006] A method for refining high-lead crude copper comprises the following steps: adding a composite impurity remover to a molten high-lead crude copper melt for refining, removing slag after a certain period of time, taking out of the furnace, and pouring to obtain refined copper;
[0007] The composite de-impurity agent comprises substance A and silicon dioxide; substance A is a mixture of one or more of phosphate and pyrophosphate.
[0008] As a preferred embodiment of the present invention, the mass percentage of substance A in the composite de-impurity agent is 60-90wt%; the mass percentage of silicon dioxide in the composite de-impurity agent is 10-40wt%.
[0009] As a preferred embodiment of the present invention, the phosphate is at least one or more mixtures of calcium phosphate, sodium phosphate and potassium phosphate; the pyrophosphate is at least one or more mixtures of calcium pyrophosphate, sodium pyrophosphate and potassium pyrophosphate.
[0010] As a preferred embodiment of the present invention, the mass percentage of lead in the high-lead blister copper is 0.2-2.0wt%.
[0011] As a preferred embodiment of the present invention, the mass ratio of the phosphate to the high-lead copper is 1:(50-500).
[0012] As a preferred embodiment of the present invention, the refining temperature is 1200-1300° C., and the holding time is 30-90 minutes.
[0013] More preferably, the refining temperature is 1250° C. and the holding time is 60 min.
[0014] As a preferred embodiment of the present invention, the compound de-impurity agent is added by pre-laying it on the bottom of the molten pool, adding it on the surface of the molten pool, or blowing it into the molten pool together with conveying equipment and compressed air.
[0015] More preferably, the compound de-impurity agent is blown into the molten pool together with compressed air through a conveying device.
[0016] As a preferred embodiment of the present invention, the pressure of the compressed air is 0.30-0.45 MPa.
[0017] Compared with the prior art, the beneficial effects of the present invention are as follows: the present invention forms a new type of composite de-doping agent with phosphate and / or pyrophosphate and silicon dioxide, and generates a (PbO)5·P2O5·SiO2 slag phase with the impurity Pb, thereby achieving efficient removal of impurity lead, and can also promote the composite de-doping agent to react with the impurities arsenic, antimony and bismuth to form slag to remove impurities such as arsenic, antimony and bismuth. Therefore, the present invention provides a refining method for high-lead crude copper, which can remove lead in a one-step directional manner while assisting in the removal of impurities such as arsenic, antimony and bismuth. In addition, the composite de-doping agent has a wide source of raw materials, is easy to operate, has a high removal efficiency, can effectively shorten the reaction time, reduce copper loss in the de-doping process, and greatly reduce the unit operation production cost, and is suitable for large-scale promotion and application. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a refined copper sample prepared by the refining method of high-lead crude copper in Example 1. DETAILED DESCRIPTION
[0019] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0020] Example 1
[0021] A method for refining high-lead crude copper comprises the following steps: 20.0 kg of high-lead crude copper (containing 96.184 wt% Cu, 1.045 wt% Pb, 0.449 wt% As, 0.839 wt% Sb, and 0.116 wt% Bi) and 0.10 kg of a composite impurity remover composed of 80 wt% calcium phosphate and 20.0 wt% silicon dioxide are used as raw materials for crude copper fire refining experiments. The high-lead crude copper raw material is added into a smelting furnace and melted, and the composite impurity remover is pre-laid on the bottom of a medium-frequency induction smelting furnace, and the stirring method is only to stir the copper melt by medium-frequency induction smelting, and the mixture is kept warm at a refining temperature of 1200°C for 40 minutes, and the slag is removed from the furnace and poured to obtain the following: Figure 1 Refined copper sample shown.
[0022] After the copper ingot is cooled, a copper cylinder with a diameter of 3.0 cm and a height of 1.0 cm is cut from the center of the sample using wire cutting. The copper cylinder is used as a sample for testing. One side is polished with 500 mesh and 1000 mesh metallographic sandpaper, and then finely polished with W1 type diamond spray polishing paste (about 10000 mesh) in conjunction with a polishing machine. In order to remove the polishing agent remaining on the surface, the sample is cleaned with ultrapure water, and the polished side is placed up in a beaker filled with ultrapure water and ultrasonicated for 15 minutes using an ultrasonic machine. After the ultrasonic treatment is completed, the sample surface is rinsed with alcohol, dried with a hot air gun, and bagged for X-ray fluorescence spectroscopy analysis of impurity content. The results of some element analysis of the copper sample XRF after refinement in Example 1 are shown in Table 1.
[0023] Table 1 XRF analysis results of some elements of copper samples after refining (wt%)
[0024] sample Cu Pb As Sb Bi High lead crude copper raw material (wt%) 96.184 1.045 0.449 0.839 0.116 Refined copper sample (wt%) 98.853 0.153 0.086 0.198 0.023 Impurity removal rate (%) / 85.4 80.8 76.4 80.2
[0025] Example 2
[0026] A refining method for high-lead crude copper comprises the following steps: 30.0 kg of high-lead crude copper (containing 98.301 wt% of Cu, 0.341 wt% of Pb, 0.184 wt% of As, 0.140 wt% of Sb, and 0.058 wt% of Bi) and 0.10 kg of a composite impurity remover composed of 60% of calcium phosphate and 40.0 wt% of silicon dioxide are used as raw materials for crude copper fire refining experiments. The high-lead crude copper raw material is added into a smelting furnace and melted, the composite impurity remover is directly added to the surface of the copper melt, the copper melt is stirred only by medium-frequency induction smelting, the temperature is kept at a refining temperature of 1200°C for 60 minutes, slag is removed, the copper melt is taken out of the furnace, and casting is performed.
[0027] After the copper ingot is cooled, a copper cylinder with a diameter of 3.0 cm and a height of 1.0 cm is cut from the center of the sample using wire cutting. The copper cylinder is used as a sample for testing. One side is polished with 500 mesh and 1000 mesh metallographic sandpaper, and then finely polished with W1 type diamond spray polishing paste (about 10000 mesh) in conjunction with a polishing machine. In order to remove the polishing agent remaining on the surface, the sample is cleaned with ultrapure water, and the polished side is placed up in a beaker filled with ultrapure water and ultrasonicated for 15 minutes using an ultrasonic machine. After the ultrasonic treatment is completed, the sample surface is rinsed with alcohol, dried with a hot air gun, and bagged for X-ray fluorescence spectroscopy analysis of impurity content. The results of XRF analysis of some elements of the copper sample after refinement in Example 2 are shown in Table 2.
[0028] Table 2 XRF analysis results of some elements of copper samples after refining (wt%)
[0029] sample Cu Pb As Sb Bi High lead copper raw material (wt%) 98.301 0.341 0.184 0.140 0.058 Refined copper sample (wt%) 99.354 0.088 0.052 0.059 0.023 Impurity removal rate (%) / 74.2 71.7 57.9 60.3
[0030] Example 3
[0031] A refining method for high-lead crude copper comprises the following steps: 20.0 kg of high-lead crude copper (containing 97.895 wt% of Cu, 0.787 wt% of Pb, 0.402 wt% of As, 0.286 wt% of Sb, and 0.133 wt% of Bi) and 0.12 kg of a composite impurity remover composed of 52.8 wt% of potassium phosphate, 17.2 wt% of sodium pyrophosphate, and 30.0 wt% of silicon dioxide are used as raw materials for crude copper fire refining experiments. The high-lead crude copper raw material is added into a smelting furnace and melted, the composite impurity remover is directly added to the surface of the copper melt, the copper melt is stirred only by medium frequency induction smelting, the temperature is kept at a refining temperature of 1250°C for 30 minutes, slag is removed, the copper melt is taken out of the furnace, and casting is performed.
[0032] After the copper ingot is cooled, a copper cylinder with a diameter of 3.0 cm and a height of 1.0 cm is cut from the center of the sample using wire cutting. The copper cylinder is used as a sample for testing. One side of the copper cylinder is polished with 500 mesh and 1000 mesh metallographic sandpaper, and then finely polished with a W1 type diamond spray polishing paste (about 10000 mesh) in conjunction with a polishing machine. To remove the polishing agent remaining on the surface, the sample is cleaned with ultrapure water, and the polished side is placed up in a beaker filled with ultrapure water and ultrasonicated for 15 minutes using an ultrasonic machine. After the ultrasonic treatment is completed, the sample surface is rinsed with alcohol, and dried with a hot air gun, and the impurity content is analyzed by X-ray fluorescence spectrometry in a bag. The results of some element analysis of the copper sample XRF after refinement in Example 3 are shown in Table 3.
[0033] Table 3 XRF analysis results of some elements of copper samples after refining (wt%)
[0034] sample Cu Pb As Sb Bi High lead copper raw material (wt%) 97.895 0.787 0.402 0.286 0.133 Refined copper sample (wt%) 98.896 0.096 0.067 0.072 0.039 Impurity removal rate (%) / 87.8 83.3 74.8 70.7
[0035] Example 4
[0036] A refining method for high-lead crude copper comprises the following steps: 20.0 kg of high-lead crude copper (containing 98.195 wt% of Cu, 0.545 wt% of Pb, 0.225 wt% of As, 0.419 wt% of Sb, and 0.116 wt% of Bi) and 0.065 kg of a composite impurity remover composed of 55.0 wt% of sodium phosphate, 25.0 wt% of potassium pyrophosphate, and 20.0 wt% of silicon dioxide are used as raw materials for crude copper fire refining experiments. The high-lead crude copper raw material is added into a smelting furnace and melted, the composite impurity remover is directly added to the surface of the copper melt, the copper melt is stirred only by medium-frequency induction smelting, the temperature is kept at a refining temperature of 1250°C for 60 minutes, slag is removed, the copper melt is taken out of the furnace, and casting is performed.
[0037] After the copper ingot is cooled, a copper cylinder with a diameter of 3.0 cm and a height of 1.0 cm is cut from the center of the sample using wire cutting. The copper cylinder is used as a sample for testing. One side of the copper cylinder is polished with 500 mesh and 1000 mesh metallographic sandpaper, and then finely polished with a W1 type diamond spray polishing paste (about 10000 mesh) in conjunction with a polishing machine. To remove the polishing agent remaining on the surface, the sample is cleaned with ultrapure water, and the polished side is placed up in a beaker filled with ultrapure water and ultrasonicated for 15 minutes using an ultrasonic machine. After the ultrasonic treatment is completed, the sample surface is rinsed with alcohol, and dried with a hot air gun, and the impurity content is analyzed by X-ray fluorescence spectrometry in a bag. The results of XRF analysis of some elements of the copper sample after refinement in Example 4 are shown in Table 4.
[0038] Table 4 XRF analysis results of some elements of copper samples after refining (wt%)
[0039] sample Cu Pb As Sb Bi High lead copper raw material (wt%) 98.195 0.545 0.225 0.419 0.116 Refined copper sample (wt%) 99.061 0.046 0.017 0.063 0.028 Impurity removal rate (%) / 91.6 92.4 85.0 75.9
[0040] Example 5
[0041] A refining method for high-lead crude copper comprises the following steps: 25.0 kg of high-lead crude copper (containing 96.683 wt% of copper, 1.836 wt% of Pb, 0.362 wt% of As, 0.489 wt% of Sb, and 0.351 wt% of Bi) and 0.26 kg of a composite impurity remover consisting of 60.0 wt% of potassium phosphate, 30.0 wt% of calcium pyrophosphate, and 10.0 wt% of silicon dioxide are used as raw materials for crude copper fire refining experiments. The high-lead crude copper raw material is added into a smelting furnace and melted, the composite impurity remover is directly added to the surface of the copper melt, the copper melt is stirred only by medium frequency induction smelting, the temperature is kept at a refining temperature of 1300°C for 90 minutes, slag is removed, the copper melt is taken out of the furnace, and casting is performed.
[0042] After the copper ingot is cooled, a copper cylinder with a diameter of 3.0 cm and a height of 1.0 cm is cut from the center of the sample using wire cutting. The copper cylinder is used as a sample for testing. One side of the copper cylinder is polished with 500 mesh and 1000 mesh metallographic sandpaper, and then finely polished with a W1 type diamond spray polishing paste (about 10000 mesh) in conjunction with a polishing machine. To remove the polishing agent remaining on the surface, the sample is cleaned with ultrapure water, and the polished side is placed upward in a beaker filled with ultrapure water and ultrasonicated for 15 minutes using an ultrasonic machine. After the ultrasonic treatment is completed, the sample surface is rinsed with alcohol, and dried with a hot air gun, and the impurity content is analyzed by X-ray fluorescence spectrometry in a bag. The impurity removal rate in the copper sample after refinement in Example 5 is shown in Table 5.
[0043] Table 5 XRF analysis results of some elements of copper samples after refining (wt%)
[0044] sample Cu Pb As Sb Bi High lead copper raw material (wt%) 96.683 1.836 0.362 0.489 0.351 Refined copper sample (wt%) 98.749 0.246 0.046 0.103 0.084 Impurity removal rate (%) / 86.6 87.3 79.0 76.0
[0045] Example 6
[0046] A refining method for high-lead crude copper comprises the following steps: 20.0 kg of high-lead crude copper (containing 96.184 wt% of Cu, 1.045 wt% of Pb, 0.449 wt% of As, 0.839 wt% of Sb, and 0.116 wt% of Bi) and 0.855 kg of a composite impurity remover composed of 80 wt% of calcium pyrophosphate and 20.0 wt% of silicon dioxide are used as raw materials for crude copper fire refining experiments. The high-lead crude copper raw material is added into a smelting furnace and melted, the composite impurity remover is pre-laid on the bottom of a medium-frequency induction smelting furnace, the stirring of the copper melt is performed only by medium-frequency induction smelting, the copper melt is kept warm for 40 minutes at a refining temperature of 1200°C, slag is removed, the furnace is unloaded, and pouring is performed.
[0047] After the copper ingot is cooled, a copper cylinder with a diameter of 3.0 cm and a height of 1.0 cm is cut from the center of the sample using wire cutting. The copper cylinder is used as a sample for testing. One side of the copper cylinder is polished with 500 mesh and 1000 mesh metallographic sandpaper, and then finely polished with a W1 type diamond spray polishing paste (about 10000 mesh) in conjunction with a polishing machine. To remove the polishing agent remaining on the surface, the sample is cleaned with ultrapure water, and the polished side is placed up in a beaker filled with ultrapure water and ultrasonicated for 15 minutes using an ultrasonic machine. After the ultrasonic treatment is completed, the sample surface is rinsed with alcohol, and dried with a hot air gun, and the impurity content is analyzed by X-ray fluorescence spectrometry in a bag. The results of XRF analysis of some elements of the copper sample after refinement in Example 6 are shown in Table 6.
[0048] Table 6 XRF analysis results of some elements of copper samples after refining (wt%)
[0049] sample Cu Pb As Sb Bi High lead copper raw material (wt%) 96.184 1.045 0.449 0.839 0.116 Refined copper sample (wt%) 99.237 0.359 0.133 0.227 0.044 Impurity removal rate (%) / 65.6 70.3 73.0 62.3
[0050] Comparative Example 1
[0051] The only difference between the refining method of high-lead crude copper in this comparative example and that in Example 1 is that the compound impurity remover is composed of 80wt% calcium phosphate and 20wt% calcium pyrophosphate. The impurity removal rate of the copper sample after refining in Comparative Example 1 is shown in Table 7.
[0052] Comparative Example 2
[0053] The only difference between the refining method of a high-lead crude copper in this comparative example and that in Example 1 is that the compound impurity removal agent is calcium phosphate. The impurity removal rate in the copper sample after refining in Comparative Example 2 is shown in Table 7.
[0054] Comparative Example 3
[0055] The only difference between the refining method of a high-lead crude copper in this comparative example and that in Example 1 is that the compound de-impurity agent is silicon dioxide. The impurity removal rate in the copper sample after refining in Comparative Example 3 is shown in Table 7.
[0056] Comparative Example 4
[0057] The only difference between the refining method of high-lead crude copper in this comparative example and that in Example 1 is that the compound impurity removal agent is calcium pyrophosphate. The impurity removal rate of the copper sample after refining in Comparative Example 4 is shown in Table 7.
[0058] Table 7
[0059]
[0060] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for refining high-lead crude copper, characterized in that: The method comprises the following steps: adding a compound decontamination agent to a molten high-lead crude copper melt for refining, removing slag after keeping the slag for a certain period of time, taking the slag out of the furnace, and pouring the refined copper; The composite de-impurity agent comprises substance A and silicon dioxide; substance A is a mixture of one or more of phosphate and pyrophosphate.
2. The method for refining high-lead blister copper according to claim 1, characterized in that: The mass percentage of substance A in the composite de-impurity agent is 60-90wt%; the mass percentage of silicon dioxide in the composite de-impurity agent is 10-40wt%.
3. The method for refining high-lead blister copper according to claim 1, characterized in that: The phosphate is a mixture of at least one or more of calcium phosphate, sodium phosphate and potassium phosphate; the pyrophosphate is a mixture of at least one or more of calcium pyrophosphate, sodium pyrophosphate and potassium pyrophosphate.
4. The method for refining high-lead blister copper according to claim 1, characterized in that: The mass percentage of lead in the high-lead crude copper is 0.2-2.0wt%.
5. The method for refining high-lead blister copper according to claim 1, characterized in that: The mass ratio of the phosphate to the high-lead copper is 1:(50-500).
6. The method for refining high-lead blister copper according to claim 1, characterized in that: The refining temperature is 1200-1300° C., and the insulation time is 30-90 minutes.
7. The method for refining high-lead blister copper according to claim 1, characterized in that: The compound de-impurity agent is added in the following ways: pre-laying it on the bottom of the molten pool, adding it on the surface of the molten pool, or blowing it into the molten pool together with conveying equipment and compressed air.
8. The method for refining high-lead blister copper as claimed in claim 7, characterized in that: The pressure of the compressed air is 0.30-0.45 MPa.